Mergers & acquisitions and innovation performance in the telecommunications equipment industry - Tseveen Gantumur; Andreas Stephan (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The telecommunications in the 1990s witnessed an enormous worldwide round of Mergers & Acquisitions (M&A). This paper examines the innovation determinants of M&A activity and the consequences of M&A transactions on the technological potential and the innovation performance. We examine the telecommunications equipment industry over the period 1988-2002 using a newly constructed data set with firm-level data describing M&A and innovation activity as well as financial characteristics. Based on a matching propensity score procedure, the study provides evidence that M&A realize significantly positive changes to the firm's post-merger innovation performance.
Keywords: L63; O30; L10; 330; Mergers & Acquisitions; Innovation Performance; Telecommunications Equipment Industry; Telekommunikationsgeräteindustrie; Fusion; Übernahme; Innovation; Welt